2022
DOI: 10.1177/13506501221074811
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the steady state characteristics of noncircular journal bearings lubricated with ferrofluid under concentric finite wire magnetic field

Abstract: The aim of the present work is to investigate the steady state performance of noncircular hydrodynamic two, three and four lobe journal bearings, lubricated with ferrofluid under concentric finite wire magnetic field. Applying momentum and continuity equation, for ferrofluid under the applied magnetic field, modified Reynolds equation is obtained. Assuming linear behaviour for the magnetic material of the ferrofluid, the Reynolds equation is solved, using finite element technique to obtain pressure distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…The results indicated that with increasing magnetic force coefficient, side leakage in noncircular bearings and friction coefficient was significantly reduced and improvement in load bearing capacity was seen at different operating conditions especially in two lobe noncircular bearing. 35 From the above literature, it has been observed that various experimental and theoretical studies for FF were conducted in the past on different tribosystems. Still, detailed tribo-testing used for permanent magnet-based new designs must be included for FF-based tribosystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that with increasing magnetic force coefficient, side leakage in noncircular bearings and friction coefficient was significantly reduced and improvement in load bearing capacity was seen at different operating conditions especially in two lobe noncircular bearing. 35 From the above literature, it has been observed that various experimental and theoretical studies for FF were conducted in the past on different tribosystems. Still, detailed tribo-testing used for permanent magnet-based new designs must be included for FF-based tribosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that with increasing magnetic force coefficient, side leakage in noncircular bearings and friction coefficient was significantly reduced and improvement in load bearing capacity was seen at different operating conditions especially in two lobe noncircular bearing. 35…”
Section: Introductionmentioning
confidence: 99%